BOS Funds Keep Being Misused: APIP, What’s Your Next Move? - Firmansyah, Amrie; Khairin, Mochamad Yahdi (Polytechnic of State Finance STAN, 2024)
This study aims to analyze the increasing misuse of School Operational Assistance (BOS) funds and evaluate the role of the Government's Internal Supervisory Apparatus (APIP) in its oversight. The main focus of this research is to identify solutions to improve the supervisory system so that BOS funds can be managed accountably and effectively. This study uses a qualitative approach with a literature review method. Data were collected from various sources, such as academic journals, oversight reports, and government regulations related to BOS fund management. The analysis was conducted to evaluate the effectiveness of APIP’s supervision and identify obstacles faced in managing BOS funds at the school level. The results show that APIP’s oversight of BOS funds has not been effective, as indicated by the increasing number of misuse cases. Factors such as limited human resources, poor internet access, and high workloads are major challenges. The synergy between central and regional APIP, the development of an information technology-based supervision system, and the strengthening of oversight culture are needed to address these issues. This research contributes to providing practical recommendations for enhancing the supervision of BOS funds through better collaboration between APIP, the Education Office, and schools. Additionally, this study offers ideas for developing an internet-based management system to improve the accountability and transparency of BOS fund management.